(untitled) (Pedagogy of Higher and Secondary Education, 2012)
Katerusha A. V. Technology of use of didactic conditions activation of students’ cognitive activity in English classes. The author substantiates the theory didactic conditions that ensure activation of the cognitive activity of students in classes in English. The notion of «a didactic condition», revealed the author’s vision of the formation of motivation of students learning the English language of non-special faculties.